How University Spin-offs Develop Opportunities: An exploratory study in how university spin-offs find, identify, and recognize opportunities - Lindbom, Emil; Jonsson, Linus (My University, 2022)
In recent years universities have seen a push to commercialise its academic advance- ment, pursuing a so called ’third mission’. This has led to an increase in university affiliated spin-offs companies trying to exploit academic research for monetary and societal benefits. The process of how opportunities emerge and are captured by entrepreneurs have been examined thoroughly in literature. However, within a uni- versity context and its unique environment the phenomena have not been studied in detail. Thus, this thesis adds to the literature by thoroughly examining how the process of opportunity recognition develop within university spin-offs. The study was conducted at Chalmers University of Technology in Gothenburg, where 11 uni- versity spin-offs, which all had recognized an opportunity, were interviewed about their journey of finding and recognizing opportunities. The study found that the general literature on opportunity recognition can adequately explain most of the phenomenon observed within the unique context of University Spin-offs. However, the study highlights new factors that indicate to having an impact on opportunity recognition process. Using entrepreneurial students as surrogate entrepreneurs was common and was deemed effective in order to survive the long process of recognizing an opportunity. Furthermore, soft money seems critical to provide enough runway to stay afloat up until an opportunity has been recognized.
Keywords: University Spin-Offs; Opportunities; Entrepreneurship; Opportunity Recognition